Tattoos and Information: Mapping the Landscape of Tattoo Research. Issue 1 (13th October 2021) - Krtalić, Maja; Campbell‐Meier, Jennifer; Bell, Rachel
Abstract: This paper is the initial discussion of a larger project Tattoo and Information, exploring tattoos as an information and communication phenomenon from multicultural perspectives and various use purposes. The overall purpose of the project is to provide insight into information seeking and experience in the context of tattoos to identify information literacy, visual literacy and cultural literacy skills as well as communications skills necessary for a successful tattoo experience in Aotearoa New Zealand. In this paper, we present findings from the literature review accompanied by preliminary insights from four interviews. The findings reflect thematic areas of research focusing on tattoos and gaps that exist. We used interviews to capture what topics emerge from tattoo narratives and whether they align with topics and gaps identified in the literature review. Based on the findings, we identify areas for future research.